Manajemen Organisasi Perpustakaan - Makmur Syukri; Ade Putra (Journal on Education, 2023)
School library management is basically the process of optimizing human, material and budget contributions to achieve library goals. The organizational structure of the national library published through the National Library Regulation of the Republic of Indonesia Number 4 of 2020 concerning the Organization and Work Procedures of the National Library. Article 5 explains in general that the national library consists of the Head, Main Secretariat, Deputy for the Development of Library Materials and Information Services; Deputy for Library Resources Development; Data and information Center; Librarian Development Center, Education and Training Center, Inspectorate, Bung Karno Proclaimer Library Technical Implementation Unit; and the Proclaimer Bung Hatta Library Technical Implementation Unit. Information technology in school libraries is technology used to create, store, change and use information in all its forms for the purposes of school library management and services. Each library must make a budget plan and submit it to its parent institution, or other institution that is obliged to provide a budget to the librar School library management is the process of influencing all personnel who support the implementation of school library operations in order to achieve the goals of organizing libraries in schools.